Unclassified sudden infant death due to congenital long QT syndrome with TRPM4 mutation - Jasleen Kaur; Ratna Dua Puri; Sharmila B Mukherjee; Bijal Vyas (Indian Pediatrics Case Reports, 2021)
Background: Congenital long QT syndrome (cLQTS) are heritable disorders due to genetic mutations causing prolonged corrected QT (QTc) interval that may result in fatal arrhythmias. Clinical Description: A well 20-day-old, exclusively breastfed boy had an episode of unresponsiveness with no other symptoms. There was a history of four previous unexplained infantile deaths after similar complaints. General and systemic examination was normal. The differential diagnoses were neonatal apnea, seizures, and inborn errors of metabolism. Management: Sepsis, hypoglycemia, and electrolyte imbalance were ruled out. Electrocardiography (ECG), chest radiograph, and echocardiograph were normal. Ultrasonogram of the cranium ruled out structural abnormality and bleed. Electroencephalogram was normal. First-line metabolic investigations were normal. On day 28 of life, he had a recurrent episode of apnea. ECG evaluation during this episode revealed a prolonged QTc interval. Suspecting cLQTS, Trio Whole Exome Sequencing for mutations in the cLQTS susceptibility genes was performed in the proband and parents. A heterozygous variation, c.290C>T; p.Thr97Met in TRPM4 was identified in the symptomatic neonate and asymptomatic mother, suggesting autosomal dominant inheritance. The baby was started on oral propranolol, but succumbed at 8 weeks. The mother was referred for cardiac management and parents counseled about possible prenatal diagnosis in subsequent pregnancies. Conclusion: cLQTS should be suspected in neonatal apnea, when no other cause is appreciable. A normal ECG does not exclude cLQTS. If there is a strong suspicion, repeat ECGs and appropriate genetic testing should be done. Patients should be managed according to standard guidelines.